AN ECOLINGUISTICS ANALYSIS OF THE WIND GOURD OF LA’AMAOMAO - Kristiawan Indriyanto (International Journal of Humanity Studies (IJHS), 2021)
This study foregrounds the Native Hawai’ians’ interconnection between culture and nature through ecolinguistic analysis of the Wind Gourd of La’amaomao. The language use in this Hawai’ian folktale emphasizes the reverence Hawai’ian people have toward their environment based on familial kinship. The analysis mainly focuses on two aspects of language use, based on Stibbe’s theory of ecolinguistic, ideology/discourse and evaluation/appraisal. The study also posits the ecosophy/ecological philosophy derived from the text in line with the current state of environmental crisis.  The study argues that the discourse employed in the text is positive, based on recognizing the need of sustainability. The positive discourse is also reflected through close emotional connection between people and place which is reflected in wind naming pattern and Hawai’ian place names. Secondly, nature is also appraised positively as seen in the celebratory tone and vocabulary used. The study concludes that alternative way of perceiving the environment, as seen from the reading of the Wind Gourd of La’amaomao should be considered as a critique toward Western anthropocentrism.